The Stability of the WHO Reference Thromboplastin NIBS & C 67/40 - Ingram, G I C (Thrombosis and Haemostasis, 1979)
The International Reference Preparation of human brain thromboplastin coded 67/40 has been thought to show evidence of instability. The evidence is discussed and is not thought to be strong; but it is suggested that it would be wise to replace 67/40 with a new preparation of human brain, both for this reason and because 67/40 is in a form (like Thrombotest) in which few workers seem to use human brain. A plain preparation would be more appropriate; and a freeze-dried sample of BCT is recommended as the successor preparation. The opportunity should be taken also to replace the corresponding ox and rabbit preparations. In the collaborative study which would be required it would then be desirable to test in parallel the three old and the three new preparations. The relative sensitivities of the old preparations could be compared with those found in earlier studies to obtain further evidence on the stability of 67/40; if stability were confirmed, the new preparations should be calibrated against it, but if not, the new human material should receive a calibration constant of 1.0 and the new ox and rabbit materials calibrated against that.The types of evidence available for monitoring the long-term stability of a thromboplastin are discussed.